Knowledge management: A roadmap for innovation in SMEs' sector of Azad Jammu & Kashmir - Iftikhar Hussain; Amber Qurashi; Ghulam Mujtaba; Muhammad Arfaq Waseem; Zafar Iqbal (Journal of Global Entrepreneurship Research, 2019)
In this empirical study, we have examined the impact of knowledge management on organizational innovation capacity. Ultimate objective of existing research was to explore the role of knowledge management in encouraging innovation capacity in SMEs. Furthermore, this study also described role of knowledge management process to enhance knowledge repositories of SMEs. In order to understand knowledge management-innovation relationship, we collected data from SMEs across Azad Jammu and Kashmir. It was found that knowledge identification/creation, knowledge collection, knowledge organizing, knowledge dissemination, and knowledge application have positive and significant impact on innovation capacity of the SMEs in AJ&K. Implications of the study were also discussed.
Keywords: 650; SMEs; Managers; Knowledge management; Innovation; Knowledge organizing; Knowledge creation; Knowledge dissemination; Knowledge application